Aurora kinase A controls meiosis I progression in mouse oocytes - Saskova, Adela; Solc, Petr; Baran, Vladimir; Kubelka, Michal; Schultz, Richard M; Motlik, Jan (Cell cycle (Georgetown, Tex.), 2008)
Aurora kinase A (AURKA), which is a centrosome-localized serine/threonine kinase crucial for cell cycle control, is critically involved in centrosome maturation and spindle assembly in somatic cells. Active T288 phosphorylated AURKA localizes to the centrosome in the late G(2) and also spreads to the minus ends of mitotic spindle microtubules. AURKA activates centrosomal CDC25B and recruits cyclin B1 to centrosomes. We report here functions for AURKA in meiotic maturation of mouse oocytes, which is a model system to study the G(2) to M transition. Whereas AURKA is present throughout the entire GV-stage oocyte with a clear accumulation on microtubule organizing centers (MTOC), active AURKA becomes entirely localized to MTOCs shortly before germinal vesicle breakdown. In contrast to somatic cells in which active AURKA is present at the centrosomes and minus ends of microtubules, active AURKA is mainly located on MTOCs at metaphase I (MI) in oocytes. Inhibitor studies using Roscovitine (CDK1 inhibitor), LY-294002 (PI3K inhibitor) and SH-6 (PKB inhibitor) reveal that activation of AURKA localized on MTOCs is independent on PI3K-PKB and CDK1 signaling pathways and MOTC amplification is observed in roscovitine- and SH-6-treated oocytes that fail to undergo nuclear envelope breakdown. Moreover, microinjection of Aurka mRNA into GV-stage oocytes cultured in 3-isobutyl-1-methyl xanthine (IBMX)-containing medium to prevent maturation also results in MOTC amplification in the absence of CDK1 activation. Overexpression of AURKA also leads to formation of an abnormal MI spindle, whereas RNAi-mediated reduction of AURKA interferes with resumption of meiosis and spindle assembly. Results of these experiments indicate that AURKA is a critical MTOC-associated component involved in resumption of meiosis, MTOC multiplication, proper spindle formation and the metaphase I-metaphase II transition.
Keywords: Aurora Kinases; blastodisk; Humans; HeLa buňky; aparát dělícího vřeténka; Blastodisc; Cell Cycle; Phosphatidylinositol 3-Kinases; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Protein Binding; Aurora kinasa A; Female; protein-serin-threoninkinasy; myši inbrední BALB C; Meiosis; lidé; zvířata; myši; Aurora Kinase A; buňky NIH 3T3; myši inbrední C57BL; Mice; oocyty; meióza; protoonkogenní proteiny c-akt; NIH 3T3 Cells; Protein Serine-Threonine Kinases; Proto-Oncogene Proteins c-akt; ženské pohlaví; HeLa Cells; Spindle Apparatus; fosfatidylinositol-3-kinasy; Mice, Inbred C57BL; vazba proteinů; organizační centrum mikrotubulů; Microtubule-Organizing Center; kinasy Aurora; Animals; Oocytes; buněčný cyklus; Mice, Inbred BALB C